Mode-selective excitation of an infrared-inactive phonon mode in diamond using mid-infrared free electron laser. (9th September 2021) - Akasegawa, Rei; Zen, Heishun; Hachiya, Kan; Yoshida, Kyohei; Goto, Takuya; Sagawa, Takashi; Ohgaki, Hideaki
Abstract: The direct demonstration was achieved for the selective excitation of the infrared-inactive T 2g mode (1332 cm −1 ) in the single crystal diamond by two-photon excitation using a mid-infrared free electron laser (MIR-FEL) as pump light. Anti-Stokes Raman scattering light at around −1339 cm −1 was observed with cooling at 5 K only when MIR-FEL whose wavenumber was that of one-half of the T 2g mode, 666 cm −1, was irradiated. Update of the probe system, i.e. the introduction of the image intensified CCD, made it possible to probe the scattering signal with a lower laser power density compared to our previous study, and it relieved the surface damage on the sample accompanied by laser irradiations which induced a red-shift and a band broadening of the mode in the previous study.